The Aspergillus flavus Spermidine Synthase (spds) Gene, Is Required for Normal Development, Aflatoxin Production, and Pathogenesis During Infection of Maize Kernels - Majumdar, Rajtilak; Lebar, Matt; Mack, Brian; Minocha, Rakesh; Minocha, Subhash; Carter-Wientjes, Carol; Sickler, Christine; Rajasekaran, Kanniah; Cary, Jeffrey W. (Frontiers in Plant Science, 2018)
Aspergillus flavus is a soil-borne saprophyte and an opportunistic pathogen of both humans and plants. This fungus not only causes disease in important food and feed crops such as maize, peanut, cottonseed and tree nuts but also produces the toxic and carcinogenic secondary metabolites (SMs) known as aflatoxins. Polyamines (PAs) are ubiquitous polycations that influence normal growth, development, and stress responses in living organisms and have been shown to play a significant role in fungal pathogenesis. Biosynthesis of spermidine (Spd) is critical for cell growth as it is required for hypusination-mediated activation of eukaryotic initiation (translational) factor 5A (eIF5A), and other biochemical functions. The tri-amine Spd is synthesized from the di-amine putrescine (Put) by the enzyme spermidine synthase (Spds). Inactivation of spds resulted in a total loss of growth and sporulation in vitro which could be partially restored by addition of exogenous Spd. Complementation of the Δspds mutant with a wild type (WT) A. flavus spds gene restored the WT phenotype. In WT A. flavus, exogenous supply of Spd (in vitro) significantly increased the production of sclerotia and SMs. Infection of maize kernels with the Δspds mutant resulted in a significant reduction in fungal growth, sporulation, and aflatoxin production compared to controls. Quantitative PCR of Δspds mutant infected seeds showed down-regulation of aflatoxin biosynthetic genes in the mutant compared to WT A. flavus infected seeds. Expression analyses of PA metabolism/transport genes during A. flavus-maize interaction showed significant increase in the expression of arginine decarboxylase (Adc) and S-adenosylmethionine decarboxylase (Samdc) genes in the maize host and PA uptake transporters in the fungus. The results presented here demonstrate that Spd biosynthesis is critical for normal development and pathogenesis of A. flavus and pre-treatment of a Δspds mutant with Spd or Spd uptake from the host plant, are insufficient to restore WT levels of pathogenesis and aflatoxin production during seed infection. The data presented here suggest that future studies targeting spermidine biosynthesis in A. flavus, using RNA interference-based host-induced gene silencing approaches, may be an effective strategy to reduce aflatoxin contamination in maize and possibly in other susceptible crops.